Transport and migration of plutonium in different soil types and rainfall regimes. (July 2022) - Cook, Megan; Kleinschmidt, Ross; Brugger, Joël; Wong, Vanessa N.L.
Abstract: Leaching and transport of contaminants is a complex interacting system affected by a suite of environmental factors. This study demonstrates the potential significance of weather events and moisture movement when interpreting plutonium (Pu) migration and advective transport in the soil matrix. Using a column transport experiment, two soil types, a sandy soil and clay-rich soil, were spiked with 238 Pu as a tracer to observe the effect of simulated tropical and arid rainfall events on Pu mobility. Partition coefficients (Kd) were determined over a period of weeks and under varying rainfall rates to establish the impact of changing weather events on Pu mobility. The variability of these temporal Kds covers six orders of magnitude over a relatively brief time period. This demonstrates the necessity for non-static Kds to accurately describe Pu transport in these systems. The Pu Kds determined by these column transport experiments fall within the bounds of anticipated values (approximately 80–300, 000 mL g −1 ) from immobile (magnitude 10 6  mL g −1 ) to moderately mobile (magnitude 10 1  mL g −1 ). The overall transport rate, shown by a decrease in calculated Kd, increases in environments where rainfall is more episodic, such as in arid regions as opposed to the consistently abundant rainfall in tropical regions. In contrast to the 238 Pu spike, 239+240 Pu resulting from contamination from nuclear tests in the sandy soil (aged for >30 years) showed higher mobility; we hypothesise that the ageing of the contamination, in particular Pu-bearing particles, accounts for this significant increase in Pu mobility. Low intensity, high frequency events in tropical sandy soil systems containing Pu particle contamination have the potential to mobilise Pu (>10 5 decrease in calculated Kd) over shorter periods of weeks, and not years as previously assumed. This increased mobility, when applied to radioecological models using Kd as a site-specific parameter, shows that there is likely to be a continued impact (risk quotient >1) on non-human biota in tropical sandy soil ecosystems. Highlights: Advective transport has a predominant role in Pu transport through soil. Pu Kd is impacted by rainfall events and will continue to change with time. The weathering and aging of soil significantly increases Pu mobility. Non-human biota is likely to be impacted by this increased Pu mobility.